Angle Class II, division 2 malocclusion with pronounced overbite - Arno Locks (Dental Press Editora, 2012)
Angle Class II, division 2, malocclusion is characterized by a Class II molar relation associated with retroclined or vertical positioning of the upper incisors and in general an overbite. This clinical case was presented to the Brazilian Board of Orthodontics and Facial Orthopedics (BBO) as part of the requirements for becoming a BBO Diplomate . A má oclusão de Classe II divisão 2 de Angle é caracterizada pela relação molar de Classe II associada a um posicionamento vertical ou retroinclinado dos incisivos superiores e, geralmente, a uma sobremordida exagerada. O presente caso clínico foi apresentado à Diretoria do Board Brasileiro de Ortodontia e Ortopedia Facial (BBO) como parte dos requisitos para a obtenção do título de Diplomado pelo BBO.